1999
DOI: 10.1046/j.1365-3032.1999.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological response to herbivore‐induced host plant volatiles in the moth Spodoptera littoralis

Abstract: In cotton, Gossypium hirsutum (Malvacae), the volatiles emitted from the plant change in response to herbivory. Ovipositing females of the Egyptian cotton leaf worm, Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae) can discriminate between cotton plants subjected to larval feeding and undamaged plants during oviposition. In this study we investigate whether females of this moth can detect the herbivore‐induced cotton volatiles. The response of female S. littoralis antennae to volatiles collected from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 34 publications
3
46
1
Order By: Relevance
“…On the contrary, female antennae house a great number of ORNs tuned to plant volatiles 24 , which females use to find and more efficiently discriminate the future larval substrate when ovipositing. In this context, the sex pheromone emitted by calling females may act as a relevant cue for larvae to find appropriate hosts.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, female antennae house a great number of ORNs tuned to plant volatiles 24 , which females use to find and more efficiently discriminate the future larval substrate when ovipositing. In this context, the sex pheromone emitted by calling females may act as a relevant cue for larvae to find appropriate hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Fall armyworm moths were attracted to undamaged maize and mechanically damaged plants 5-6 and 24-25 h. However, no preference was exhibited between mechanically damaged plants 5-6 h and 24-25 h over undamaged plants (Fig 1). Undamaged corn plants release linalool, which is likely the compound responsible for female moth attraction (Jönsson & Anderson 1999, D'Alessandro & Turlings 2006. Mechanical damage generally does not elicit differential volatile plant blend later than 2 h unless mechanical Fig 1 Olfactory preference of Spodoptera frugiperda gravid females to volatiles emitted by undamaged corn plant (UP) and mechanically damaged corn plants (MDP) at 0-1, 5-6, and 24-25 h. All plant treatments that differed against blank (B) were compared to volatiles from undamaged plant (UP).…”
Section: Discussionmentioning
confidence: 99%
“…Volatile blend immediately released by mechanically damaged corn, irrespective of regurgitate application, is mainly composed by green leaf volatiles (GLVs) which comprise six-carbon alcohols, aldehydes, and esters (Turlings et al 1998, Hoballah & Turlings 2005. Some GLVs have been shown to be electrophysiologically active to female Spodoptera moths (Jönsson & Anderson 1999, Malo et al 2004, but no studies have shown whether female moths are attracted or repelled by GLVs. In view of that, GLVs may have masked some important volatile compounds for host location by moths, such as linalool, or even repelled.…”
Section: Discussionmentioning
confidence: 99%
“…sensilla generally respond to a threshold dose sex-pheromones between 10 -7 g and 10 -12 g (Angioy et al 2003, Boeckh and Selsam 1984, Kaissling 1971, Kaissling and Priesner 1970 and to kairomones at amounts often 10 to 100 fold higher , Hill et al 2009, Jönsson and Anderson 1999, Larsson et al 2001. It is important to mention that these experimentally derived threshold values are all relative, and should not be taken as absolute values; since volatility differs greatly amongst various compounds, and experimental factors such as the speed of airflow and the Hill et al 2009 andGhaninia et al 2008).…”
Section: Sensitivitymentioning
confidence: 99%